FLOOD MANAGEMENT STRATEGY IN THE LANDAK SUB-RIVER BASIN USING SWOT ANALYSIS - Alfaro, Aldi; Soeryamassoeka, SB; Gunarto, Danang; Umar, Umar; Yulianto, Eko (Jurnal Teknik Sipil, 2023)
The Landak sub-River Basin is part of the Kapuas River Basin which is drained by the Landak River with an area of approximately 7,921 km2. Flooding in the Landak sub-River Basin occurs every year with the number of cases tending to increase. Flooding in the Landak sub-River Basin inundates about 20 villages, which means that flood-prone areas dominate. The causes of flooding in the Landak sub-River Basin are very complex, basically caused by natural and non-natural factors. Specifically, there are many problems in the Landak sub-River Basin that are thought to trigger flooding such as land use change, decreasing catchment areas, blockages in small rivers, and so on. To identify strategic issues regarding flooding in the Landak sub-River Basin, a Focus Group Discussion (FGD) was conducted which was attended by several resource persons who were credible with the subject matter and an AHP analysis was conducted first to determine the priority scale of flood management in the Landak sub-River Basin. The result of determining the priority scale of flood management in the Landak sub-River Basin is the strengthening and implementation of regulations. The resulting strategic issues were subjected to a questionnaire that was assessed by the respondents involved during the FGD. The results obtained from this series of SWOT analyses are the formulation of strategies that are most suitable for the strategic issues of flooding in the Landak sub-River Basin using QSPM analysis, along with the determination of short-term, medium-term and long-term strategies using SFAS analysis.